2019
DOI: 10.1016/j.jiec.2019.04.017
|View full text |Cite
|
Sign up to set email alerts
|

Improved single-step extraction performance of aqueous biphasic systems using novel symmetric ionic liquids for the decolorisation of toxic dye effluents

Abstract: Highlights New symmetric ILs were used for extraction of widely used toxic textile dyes from waste water;  Low amount of eco-friendly citrate salt was applied to generate ABS;  Efficiency of 99.4% for removal of Orange II in a single step extraction was achieved;  Maximal efficiency was obtained using minimal amounts of ABS ingredients;  Recycling procedure of applied ILs was successfully tested and proposed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(7 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…the wider the two-phase region, a smaller amount of salt is needed to salt out a certain amount of ionic liquid. 38 Phase diagrams based on choline-based ionic liquids and salts ( Fig. 1 ) provide the insight into the influence of ionic liquids on the ability to form an aqueous biphasic system.…”
Section: Resultsmentioning
confidence: 99%
“…the wider the two-phase region, a smaller amount of salt is needed to salt out a certain amount of ionic liquid. 38 Phase diagrams based on choline-based ionic liquids and salts ( Fig. 1 ) provide the insight into the influence of ionic liquids on the ability to form an aqueous biphasic system.…”
Section: Resultsmentioning
confidence: 99%
“…87 Depending on the nature of the ABS components, IL can play the role of salting-in (e.g., IL and inorganic salt) or salting-out ( polymer and IL). Various IL-ABS have been successfully used to separate bioactive compounds, 88 dyes, 89 flavonoids, 90 metal anions, 91 etc. In the last 10 years, 443 research articles on IL and ABS were found in Scopus.…”
Section: Ionic Liquidsmentioning
confidence: 99%
“…To employ ILs as solvents, one must be aware of how they react with other substances, such as water and conventional solvents used in extraction and separation processes, including alcohols or carboxylic acids. 10,11 ILs, which were initially investigated for their thermophysical and thermodynamic properties, are today believed to have applications in a wide range of areas, including materials science, cell engineering, lunar mirrors, and so on. 12 The thermodynamic properties of IL ternary mixtures are not well-understood despite a large amount of research on the thermodynamic properties of ILs and their binary mixtures with organic solvents.…”
Section: Introductionmentioning
confidence: 99%
“…This is accomplished by adding the proper cosolvent to the IL or by changing the cationic or anionic component of the IL. To employ ILs as solvents, one must be aware of how they react with other substances, such as water and conventional solvents used in extraction and separation processes, including alcohols or carboxylic acids. , …”
Section: Introductionmentioning
confidence: 99%